Hubungan Promosi Dan Harga Terhadap Keputusan Aplikan Dalam Memilih Kuliah Di Politeknik LP3I Bandung - Abdur Razak; Bambang Suprayogi; Andina Dwijayanti; Yuyun Taufik; Muhammad Ridwansyah (Program Studi Administrasi Bisnis, 2026)
This study aims to analyze the relationship between promotion and price on applicants' or prospective new students' decisions in choosing a university. A quantitative approach using explanatory methods was applied by distributing questionnaires to prospective new students as the primary instrument, which were then analyzed using multiple linear regression analysis. The research findings revealed that promotion and price variables, both partially and simultaneously, have a positive and significant influence on student choice decisions. Specifically, prospective new students perceive price as an indicator of educational quality, strengthening their confidence in their choice of institution. The implications of these results emphasize the need for integration between persuasive marketing communications and tuition policies commensurate with the value of the service. Future research is expected to explore additional variables such as facilities and institutional image to provide a more comprehensive picture for higher education management in formulating recruitment strategies.